2022
DOI: 10.3389/fpls.2022.852373
|View full text |Cite
|
Sign up to set email alerts
|

A Class II KNOX Gene, KNAT7-1, Regulates Physical Seed Dormancy in Mungbean [Vigna radiata (L.) Wilczek]

Abstract: Seed dormancy in wild mungbean (Vigna radiata var. sublobata) may be useful for the breeding of cultivated mungbean (var. radiata) with pre-harvest sprouting resistance. Previous studies have identified two major quantitative trait loci (QTLs) for seed dormancy, HsA and Sdwa5.1.1+, in wild mungbean that are possibly having the same locus or linked. However, these QTLs have not been confirmed/verified and a molecular basis of seed dormancy in mungbean is not yet known. In this study, we aimed to finely map the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…It was located between SSR markers cp05137 and CEDG074b. Laosatit et al (2022) speculated that HsA and Sdwa5.1.1+ are the same loci and finely mapped Sdwa5.1.1+ using ACC41 as the source of seed dormancy; they found that the cp05137-CEDG074b interval contained two QTLs for dormancy, Sdwa5.1.1+ and Sdwa5.1.2+, with more or less equal effects.…”
Section: Seed Dormancymentioning
confidence: 99%
See 1 more Smart Citation
“…It was located between SSR markers cp05137 and CEDG074b. Laosatit et al (2022) speculated that HsA and Sdwa5.1.1+ are the same loci and finely mapped Sdwa5.1.1+ using ACC41 as the source of seed dormancy; they found that the cp05137-CEDG074b interval contained two QTLs for dormancy, Sdwa5.1.1+ and Sdwa5.1.2+, with more or less equal effects.…”
Section: Seed Dormancymentioning
confidence: 99%
“…At the Sdwa5.1.2+ region, containing five genes, Vradi07g10480, encoding calmodulin-like (CML) protein 1, is likely the gene controlling seed dormancy (Laosatit et al, 2022). Calmodulin (CaM) and CML proteins have been shown to be involved in the ABA-induced inhibition of seed germination and seedling growth.…”
Section: Seed Dormancymentioning
confidence: 99%
“…In Vigna vexillate , a major QTL, i.e., qSdwa3.1 , positively affects seed water absorption ( Amkul et al, 2020 ). KNAT7-1 , a class II KNOX gene, is identified to affect seed dormancy in green gram ( Laosatit et al, 2022 ). In green gram seeds, a high level of α-amylase activity is found positively associated with seed dormancy ( Lamichaney et al, 2018 ).…”
Section: Genetics Of Domestication-related Traits In Legumesmentioning
confidence: 99%
“…Transferase complex subunit pseudogene (TCP) has been shown to be a key player in the biosynthesis of lipids and phytohormones, such as BRs and jasmonate (JA), and to control seed germination [18][19][20]. Loss of function of knotted-related homeobox (KNOX) resulting in reduced 18:2ω-hydroxy fatty acid in the seed cutin alters cuticle layer permeability and has been shown to help regulate physical seed dormancy in M. truncatula L. and mungbean (V igna radiata [L.] Wilczek) [21]. The interaction between KNOX and growth-regulating factor (GRF)family TFs is conserved in dicotyledons, and OsGRF3 and OsGRF10 have a repressive effect on OsKN2 in rice, resulting in reductions in plant internodes and increases in adventitious root numbers at nodes [22].…”
Section: Introductionmentioning
confidence: 99%